A European Perspective on Long-Term Unemployment - Werner Eichhorst; Franziska Neder; Verena Tobsch; Florian Wozny (Institute for the Study of Labor (IZA), 2015)
In contrast to the recently decreasing unemployment rates in the EU, long-term unemployment remains at alarming levels. An economic recovery will not be sufficient to get all long-term unemployed back to work; rather, there is a need for effective policies addressing the long-term unemployed. To address these issues, this paper starts with an interpretation of standard measures of long-term unemployment and alternative measures of long-term non-employment. Next, we take a closer look at active labor market policies such as training, subsidized employment and public work and investigate which kind is most effective for the reintegration of long-term unemployed persons. Subsequently, the special role of Public Employment Services (PES) and the importance of an individual approach and targeting is stressed to increase the employability of hard-to-place and distant jobseekers from the labor market. Furthermore, we take into account the role of alternative benefit systems for working-age non-employed people. In the final section, we conclude and offer policy advice with a particular focus on the EU.
Keywords: J64; J65; J68; 330; long-term unemployment; activation; Europe; disability benefits